Glucagon-like peptide 1 receptor agonists and cancer risk: advancing precision medicine through mechanistic understanding and clinical evidence - Anqi Lin; Yanxi Ding; Zhengrui Li; Aimin Jiang; Zaoqu Liu; Hank Z. H. Wong; Quan Cheng; Jian Zhang; Peng Luo (Biomarker Research)
Abstract Glucagon-like peptide-1 receptor agonists (GLP-1RAs) have emerged as a primary first-line treatment for type 2 diabetes. This has raised concerns about their impact on cancer risk, spurring extensive research. This review systematically examines the varied effects of GLP-1RAs on the risk of different types of tumors, including overall cancer risk and specific cancers such as thyroid, pancreatic, reproductive system, liver, and colorectal cancers. The potential biological mechanisms underlying their influence on cancer risk are complex, involving metabolic regulation, direct antitumor effects, immune modulation, and epigenetic changes. A systematic comparison with other antidiabetic agents reveals notable differences in their influence on cancer risk across drug classes. Additionally, critical factors that shape the relationship between GLP-1RAs and cancer risk are thoroughly analyzed, including patient demographics, comorbidities, treatment regimens, and lifestyle factors, offering essential insights for developing individualized treatment protocols. Despite significant research progress, critical gaps remain. Future research should prioritize elucidating the molecular mechanisms behind the antitumor effects, refining individualized treatment strategies, investigating early tumor prevention applications, assessing potential benefits for non-diabetic populations, advancing the development of novel therapies, establishing robust safety monitoring frameworks, and building precision medicine decision-making platforms. These efforts aim to establish novel roles for GLP-1RAs in cancer prevention. and treatment, thereby advancing the progress of precision medicine.